Donor notification in reactive donors and their response to communication - Basnotra, Ritika M.; Sidhu, Meena D. (International Journal of Research in Medical Sciences, 2019)
Background: Blood transfusion is associated with the risk of transmitting transfusion transmissible infections (TTI) even after the thorough mandatory TTI screening of blood units. To prevent disease transmission, it is important to inform, notify and counsel the donors about their seroreactive status at the blood centre. The present study determines the response of various TTI reactive donors for post donation counselling after notification and their persistence in society as reactive donors. Methods: It was a retrospective study conducted at tertiary care center from 1May2015 to 30April2017. Re-active donors were called to the blood bank by telephonic call and letters. Reactive donors on complying at center were retested, counselled and referred to appropriate centre for further management. Results: There were 34,204 blood donations over period of two years, out of which 375[1.09%] were reactive donors. Of these HBV reactive comprises of 166/34204(0.48%), HCV were 40/34204(0.11%), HIV reactive donors comprises of 26/34204(0.07%), Syphilis 138/34204[0.40%] and there were five cases of co-infection, two for HIV+ HCV, two cases HIV+HBV and one case of co-infection with HBV+ Syphilis. A total of 375 TTI reactive donors were identified, out of which (227/375) 60.5% contacted by tele-phone calls and letters and remaining (148/375) 39.46% cannot be contacted. Out of 227 contacted donors only 117 donors reported for post donation counselling i.e. response rate of 51.54%. Conclusions: Donor notification is efficient method of curtailing TTI but undermined by communication failure with donors, resulting in persistent load of blood transmissible infectious risk.